IMPLEMENTATION OF PSYCHOWRITING PROGRAM TO IMPROVE WRITING COMPETENCE FOR SENIOR HIGH SCHOOL STUDENTS (SLTA) IN SUKAMARA, CENTRAL KALIMANTAN - Muhsin Kalida; Mulyanto Mulyanto; Rejokirono Rejokirono (UIN Sunan Kalijaga Yogyakarta, 2020)
Abstract. This study seeks to provide a method for growing interest in writing in children called the psychowriting program as an intervention. This method was given within three hours to students of Sukamara, Central Kalimantan, which amounted to 80 students. The output of this psychowriting programintervention is that students become enthusiastic to read and write and are publishing an antology book of students' work. This research is a field research with a qualitative descriptive analysis approach. Data collection methods, using interviews, observation and documentation. The results of the study, that the implementation of psychowriting methods: a) technique of creating ideas, b) technique of creating mood, and c) holistic creative learning techniques.Key words: psychowriting method, writing competence